RECLAIMING DIGITAL INTIMACY FOR YOUTH: PILOTING DIGITAL SEXUAL VIOLENCE WORKSHOPS FOR UNDER-18S DURING THE COVID-19 PANDEMIC IN ENGLAND AND IRELAND - Ging, Debbie; Ringrose, Jessica; Mendes, Kaitlynn; Horeck, Tanya; Milne, Betsy; Desborough, Karen; Castellini de la Silva, Ricardo (AoIR Selected Papers of Internet Research, 2023)
Online sexual abuse and violence have become an urgent global problem for women and girls, and in particular for poor women, women of colour and LGBTQ women (Ging and Siapera, 2019). Online sexual harassment and abuse is an especially urgent issue for young people, for whom digital spaces are key sites of communication, identity formation, self-expression and sexual interaction. The toxic dynamics that frequently underpin these complex entanglements thus pose a significant threat to ethical digital intimacy. This situation became substantially more extreme during COVID-19, with rates of online abuse and harassment rising as young people have been forced to spend more and more time online. During this period, usage of particular platforms (e.g. TikTok) dramatically increased. A substantial rise in screen time also impacted young people’s experiences and digital intimacies in important ways.This paper reports on the findings of a cross-national study conducted in England and Ireland, which explored pedagogical interventions into the continuum of online and offline sexual violence amongst young people in schools. In particular, we are interested in how different social media platforms are used to perpetuate different types of online abuse based on certain technological affordances, such as Snapchat quick adds, shout outs and streaks, and Instagram direct message and group chat features. We make a number of concrete recommendations, pointing in particular to urgent paradigm shifts in digital ethics and digital safety initiatives, with a particular focus on platform algorithims, policies and governance.